2019
DOI: 10.3390/mi10120846
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Nozzle Inclination and Process Parameters in Air-Shielding Electrochemical Micromachining

Abstract: Microstructures on metal surfaces with diameters of tens to hundreds of micrometers and depths of several micrometers to tens of micrometers can improve the performance of engineering parts. Air-shielding electrochemical micromachining (AS-EMM) is a promising method for fabricating these microstructures, owing to its advantage of high efficient and better localization. However, the machining performance is often influenced by the machining or nonmachining parameters in AS-EMM. In order to get a better machinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…Reference [ 16 ] demonstrated that the horizontal orientation of the jet is beneficial for the Jet-ECM processes to improve the machining accuracy. Reference [ 17 ] introduced the air-shielding in the Jet-ECM process and disclosed a novel scheme to improve the machining accuracy by a combination of theoretical analysis and experimental verification. Although, Jet-ECM is a promising method for creating surface structures but suffers from stray machining and less repeatability due to jet-dynamics, hydraulic-jump and requires tool-path planning for complex surface structures as in sequential machining process.…”
Section: Introductionmentioning
confidence: 99%
“…Reference [ 16 ] demonstrated that the horizontal orientation of the jet is beneficial for the Jet-ECM processes to improve the machining accuracy. Reference [ 17 ] introduced the air-shielding in the Jet-ECM process and disclosed a novel scheme to improve the machining accuracy by a combination of theoretical analysis and experimental verification. Although, Jet-ECM is a promising method for creating surface structures but suffers from stray machining and less repeatability due to jet-dynamics, hydraulic-jump and requires tool-path planning for complex surface structures as in sequential machining process.…”
Section: Introductionmentioning
confidence: 99%
“…(3) Tooling technologies and micro tool design. Wang et al [6] developed the air-shielding electrochemical micromachining (AS-EMM) process to improve the generation of microstructures on metal surfaces; Li et al [7] analyzed the effects of machining errors on the optical performance of optical aspheric components in ultra-precision diamond turning; Tucker et al [8] characterized different venting design solutions in micro molding tools and the influence of micro injection molding process parameters on air traps and adiabatic heating. (4) Applications.…”
mentioning
confidence: 99%